DETERMINANTS OF CONTRACEPTIVE USE IN RURAL POOR AREAS: EVIDENCE FROM INDONESIA - Maria Gayatri (Universitas Airlangga, 2023)
Introduction: Meeting the demands of reproductive health among women poses persistent issues, particularly for impoverished and rural women who face impediments to healthcare services. The goal of this study was to explore the factors that influence contraceptive use among poor women in Indonesian rural areas. Methods: This study is a further analysis of Indonesia Demographic and Health Survey 2017. The respondents were 10,199 poor women who lived in rural areas in Indonesia. This quantitative study is analyzed by using logistic regression adjusted for complex sample. Results: The prevalence of modern contraceptive use among respondents was 63.1% consisting of 4.4% traditional users and 58.7% modern contraceptive users. The occupation of the husband and the wish to have no more children were both linked to the usage of contraceptive methods among impoverished women in rural areas. Young women (aged 15-34) with a high parity (three and more), who had secondary education or less, who went to the health facilities, and who lived in Java-Bali were more likely to utilize contraceptive methods. Conclusion: Despite the numerous hurdles to reproductive healthcare, it is critical to focus on methods to improve contraceptive use among poor women in rural areas.